DESIGN AND IMPLEMENTATION OF LEADER FOLLOWER FLOCKING ALGORITHM ON UNMANNED GROUND VEHICLE BY VELOCITY CORRECTION USING PROPORTIONAL INTEGRAL CONTROLLER - BAHTIAR (NIM : 13311013) - AGUNG PRASDIANTO (NIM : 13311029), HAFIDZ
Research in robotics has been developed at this time. One such study was inspired by the behavior of living things such as flocking. Basically the flocking behavior is aligned movement of a group of individual to perform certain functions such as protection against predators or increase work effectiveness. Reynold first simulate the flocking of birds. After that a lot of research done flocking to be applied to the robot by various methods. This research final project used leader-follower flocking algorithms and then applied to a set of robots which is Unmanned Ground Vehicle (UGV). The algorithm also used random leader selection so the robots can maintain when there are interference with the formation. These results indicate that the leader follower algorithm can be applied to the UGV with high repeatability which is shown by the corellation coeficient close to 1, that is 0.989875. This flocking system using Proportional Integral controller with proportional coeficient (Kp) is 0.21 and the value of integral time coeficient (Ti) is 105 and coeficient of refference is 8. In this research, if the leader is disturbed then the robot can maintain formation to keep flocking system running well.